CD1d‐mediated lipid presentation by CD11c+ cells regulates intestinal homeostasis. (29th January 2018) - Sáez de Guinoa, Julia; Jimeno, Rebeca; Gaya, Mauro; Kipling, David; Garzón, María José; Dunn‐Walters, Deborah; Ubeda, Carles; Barral, Patricia
Abstract: Intestinal homeostasis relies on a continuous dialogue between the commensal bacteria and the immune system. Natural killer T (NKT) cells, which recognize CD1d‐restricted microbial lipids and self‐lipids, contribute to the regulation of mucosal immunity, yet the mechanisms underlying their functions remain poorly understood. Here, we demonstrate that NKT cells respond to intestinal lipids and CD11c + cells (including dendritic cells (DCs) and macrophages) are essential to mediate lipid presentation within the gut ultimately controlling intestinal NKT cell homeostasis and activation. Conversely, CD1d and NKT cells participate in the control of the intestinal bacteria composition and compartmentalization, in the regulation of the IgA repertoire and in the induction of regulatory T cells within the gut. These changes in intestinal homeostasis require CD1d expression on DC/macrophage populations as mice with conditional deletion of CD1d on CD11c + cells exhibit dysbiosis and altered immune homeostasis. These results unveil the importance of CD11c + cells in controlling lipid‐dependent immunity in the intestinal compartment and reveal an NKT cell–DC crosstalk as a key mechanism for the regulation of gut homeostasis. Synopsis: CD1d‐mediated crosstalk between NKT cells and CD11c + cells regulates intestinal homeostasis by shaping bacteria and immune cell populations within the gut. CD1d‐dependent presentation of lipids by CD11c + cells controls the homeostasis and activation of the intestinal NKT cells. CD1d expression on CD11c + cells contributes to the shaping of the intestinal microbiota composition. Crosstalk between NKT cells and CD11c + cells modulates the intestinal immune cell populations by regulating the IgA repertoire and the induction of regulatory T cells within the gut. Abstract : Presentation of gut microbial and self lipids to natural killer T cells is key to maintaining intestinal microbiota composition and immune cell populations.